Horse racing and the transition between rural and urban in Curitiba (1854-1873) (Revista de História Regional, 2023)
This article aims to discuss the experiences of horse racing promoted in the city of Curitiba between 1854 and 1873. The specific aim is to investigate the relationship of this dynamic with the debates between rural and urban aspects that were established in the capital of Paraná. The time frame considers the date of the first advertisement in newspapers of initiatives involving horse racing, as well as the year in which an exclusive space for the races began to operate in Curitiba. As sources were used newspapers, decrees and laws of the Province during the period in question. In the end, it was possible to consider that the horse races were indicators of the transformations that the city incorporated, especially with regard to the dynamization of urban aspects to the detriment of rural ones.
Keywords: Entertainment History, City History, Curitiba, Horse Racing, Urbanization.